Human Capital dan Kinerja Usaha melalui Women Entrepreneur's Capability pada Industri Pariwisata - Luluk Fadliyanti; Diswandi Diswandi; Mansur Afifi (Valid: Jurnal Ilmiah, 2022)
ABSTACT The purpose of this study was to determine the effect of human capital on business performance through women entrepreneurs in the tourism industry on the island of Lombok. The entrepreneur's capability of women entrepreneurs is an intervening variable in this study, which will link the level of education, business training, entrepreneurial spirit and previous experience to business performance. The data used is primary data by distributing questionnaires directly to women entrepreneurs in 5 districts and cities on the island of Lombok. And using secondary data taken from the Central Bureau of Statistics of West Nusa Tenggara and the Office of Women's Empowerment of West Nusa Tenggara Province. This study uses quantitative analysis methods, using Likert scale research instruments and Structural Equation Modeling (SEM) analysis tools, using PLS 3.0 to test hypotheses. The results of the analysis show that the variables of business training and previous experience have a positive and significant influence on women entrepreneur's capability. And women entrepreneur's capability has a positive and significant influence on the business performance of women entrepreneurs in the tourism industry on the island of Lombok. The findings in this study are the variables of business training (program design, presentation method, content and curriculum) and previous experience (length of business, business achievement and self-development) have an indirect effect on business performance (increase in sales, increase in company assets and business profitability). but through women entrepreneur's capability which includes initiative and proactiveness, knowledge and development of new products from women entrepreneurs in the tourism industry on the island of Lombok.